PENGARUH KOMPETENSI PROFESIONAL GURU AKUNTANSI TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN AKUNTANSI SMA SWASTA SE-KOTA PEKANBARU - Winari, Nova Winari; Indrawati, Henny Indrawati; ', Syakdanur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This study aims to determine the effect of the accounting skills of teachers on student achievement in high school accounting topics Private Se Pekanbaru city. This study was conducted in private SMA Se-Pekanbaru City from April 2015 to May 2015. The method used is descriptive quantitative method. Population of 35 teachers and a sample of 35 teachers. Mechanical sampling of the population saturated with the aid of samples. Data collection instruments were a matter of testing and documentation. Data analysis technique is a simple linear regression. The result showed that the competency of teachers affects student performance. This is based on the results of analyzes, calculations show Thitung> Ttabel (2,916> 2,035). So it can be concluded that the professional skills of teachers affects student performance with a contribution of 20.5% and the remaining 79.5% is influenced by other variables not examined as a family, motivation, community and others. Keywords: Influence, the professional competence of teachers, academic achievement